Comparisons between the pork Warner-Brazler shear force values of the roasting and boiling cooking methods - Fong, Michelle Wai Cheng; Ooi, Peck Toung; Sazili, Awis Qurni; Goh, Yong Meng (Veterinary Association Malaysia, 2018)
This study focuses on investigating the difference in Warner Brazler Shear Force (WBSF) values of pork meat and its reliability between roasting and boiling cooking methods. Ten samples of longissimus dorsi (LD) whole cuts from commercial three-way crosswere trimmed to a length of 4 cm thickness each. Each sample was then separated into 2 groups: Group 1:Roasted with convection oven to internal temperatures of 70°C, and Group 2: Boiled in a water bath of 80°C for 30 min until internal temperature of 70°C. A total of 57 pairs of cylindrical cores (6-7 cylindrical cores) were obtained from each cooked LD for analysis. Difference between the two cooking methods for both the shear force values were compared using pairwise student T test statistical analysis and intraclass correlation coefficient (ICC) was used to establish and quantify reproducibility for reliability of the measurements. The WBSF values for roasted pork is significantly lower (p<0.05) than the WBSF values of boiled pork, with very high ICC between both samples [r=0.905, 95% CI (0.64, 0.98)]. Bland & Altman plots subjected to limits of agreements (LOA) also showed good agreements for all the measurements. Roasting gives a lower WBSF values when compare to boiling (0.51kg difference, 10.89% difference). Both roasted and boiled cooking methods can be used to determine the shear force values of pork.